Examining the relationships between labour market mismatches, earnings and job satisfaction among immigrant graduates in Europe - Séamus McGuinness; Delma Byrne (The Economic and Social Research Institute (ESRI), 2014)
This paper uses graduate survey data and econometric methods to estimate the incidence and wage/job satisfaction effects of over-education and overskilling among immigrants graduating from EU 15 based universities in 2005. Female immigrants with shorter durations of domicile were found to have a higher likelihood of overskilling. Newly arrived immigrants incurred wage penalties' which were exacerbated by additional penalties resulting from overskilling in the male labour market and overeducation in the female labour market. Established immigrants were found to enjoy wage premia, particularly within the male labour market, with no evidence of disproportionate wage impacts arising as a consequence of mismatch. Female immigrants were generally found to have a significantly lower probability of being job satisfied relative to native female graduates.
Keywords: 330; overeducation; overskilling; immigrants; pay; job satisfaction